Gender-Based Expectations and their Effect on Mental Health Amongst Black African Immigrant Young Men Living in Canada - Omolola Olawo (York University Libraries, 2019)
Black African immigrant men's mental health is relatively understudied. This article is part of a larger study that explored the perceptions of mental health amongst African immigrant youth living in Canada. Using an interpretive description methodology, underpinned by an intersectional and critical lens, this article addresses racial, societal, and cultural expectations that could have an effect on Black African immigrant men's mental health. Eight men and women who self-identified as Black African immigrants between the ages of 18 and 25 participated in the overall study, while five participants contributed the data for this article. Masculinity as a determinant of health, the resilience of African men, and the intersections of identity and vulnerability are discussed. It is concluded that the stigma surrounding Black African men speaking out about their mental health warrants a deeper examination in relation to their mental health outcomes. Areas of further inquiry include exploring mental health service utilization amongst Black African immigrant men.